2022
DOI: 10.3390/su14116835
|View full text |Cite
|
Sign up to set email alerts
|

Field Study on the Side Resistance-Softening and Resistance-Reinforcing Effects of Large-Diameter Combined Grouting Drilled Shafts

Abstract: The traditional design method for drilled shafts rarely considers the influence of construction effect and tip resistance on side resistance, and lacks attempts to improve the performance of drilled shafts without increasing drilled shafts sizing, economic costs and carbon emissions. In this paper, the influences of construction-effect and shaft tip resistance on the side resistance of large-diameter drilled shafts before and after combined grouting were studied by full-scale field tests. The reinforcing effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Various techniques for strengthening slopes include installing anchor cables [3], building antislip structures [4], improving the soil with chemical additives [5], and utilizing a confined-toone-region precise reinforcement approach based on the processes and instability modes of landslides [6]. One practical usage procedure for geotechnical construction is to install retaining structures, such as rigid retaining walls and antislide piles, to reinforce slopes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques for strengthening slopes include installing anchor cables [3], building antislip structures [4], improving the soil with chemical additives [5], and utilizing a confined-toone-region precise reinforcement approach based on the processes and instability modes of landslides [6]. One practical usage procedure for geotechnical construction is to install retaining structures, such as rigid retaining walls and antislide piles, to reinforce slopes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bearing capacity will decrease as a result of soil stress relaxation and bearing layer disruption during drilling [41,48]. A multitude of studies have demonstrated that post-grouting is a proficient solution for rectifying construction deficiencies and enhancing the load-bearing capacity of pile foundations [8,17,18,24]. Determining the carrying capacity is an important consideration in pile foundation design, and regulations require sampling inspection of the piles' carrying capacity [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The test results indicated postgrouting was a resource-intensive foundation treatment method that was also a critical technological means of achieving green and lowcarbon construction. Hu et al, 2022a proposed that it was unable to directly evaluate its construction quality and grouting consequences since the post-grouting technique took place underground. As a result, it was important to analyze and evaluate the changes in grouting parameters during the post-grouting process (Wan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%